The Effectiveness of Empathic Love Therapy to Improve the Psychological Well-being of Families Accompanying Schizophrenia Patients in Klasaman District, Sorong - Tri Permata Sari; Adinda Shofia; Amalia Muthmainnah Lundeto; Marsya Eka Viona; Endah Dwi Nuraini (Jurnal Ners, 2025)
Schizophrenia is a serious mental disorder and is among the highest in Indonesia. Family caregivers play a crucial role in the recovery of schizophrenia patients. Being a caregiver for schizophrenia patients is not easy, as several studies have shown low psychological well-being due to the psychological burden and pressure they experience. One approach to improving the psychological well-being of families caring for schizophrenia patients is through a therapeutic approach, namely empathic love therapy (ELT). The purpose of this study was to determine the effectiveness of Empathic Love Therapy in improving the psychological well-being of families caring for schizophrenia patients in Sorong. ELT is a psychosynthetic love method that emphasizes recognizing, realizing, and loving all aspects of oneself, accompanied by personal growth and development in the form of unification with the whole self. The research method used was a quasi-experimental one-group pretest-posttest design. Psychological well-being was measured using the Psychological Well-being Scale, while Empathic Love used the Empathic Love Therapy Assessment Sheet, which consists of the General Overall Assessment (GOA) and the Specific Assessment and Reactions to Empathic Love Therapy (SAR). The Wilcoxon Signed-Rank test showed a significant difference (Z = -2.023, p = 0.043). This indicates that the Empathic Love Therapy (ELT) intervention was effective in improving the psychological well-being of family caregivers of schizophrenia patients in the Klasaman District of Sorong.